COVID-19-related changes in outpatient CPAP setup pathways for OSA are linked with decreased 30-day CPAP usage. Issue 8 (9th May 2022) - Turnbull, Chris D; Allen, Martin; Appleby, Jennifer; Brown, Richard; Bryan, Nathalie; Cooper, Ann; Cooper, Brendan G; Gillooly, Cathie; Davidson, James; Farley, Hannah; Gaspar, Ana; Gibbons, Gillian; et al.
Abstract : The COVID-19 pandemic changed continuous positive airway pressure (CPAP) setup pathways. We evaluated patients commenced on CPAP in 2019 (prepandemic) and 2020 (post-first UK wave). Face-to-face (F2F) setup numbers, with CPAP turned on, decreased from 613 patients (98.9%) in 2019, to 6 (1.1%) in 2020. In 2020, setups were F2F without CPAP turned on (403 (71.1%)), or remote (158 (27.9%)). Prepandemic median CPAP usage at first follow-up was 5.4 (2.7–6.9) hours/night and fell by 0.9 hours/night (95% CI 0.5 to 1.2, p<0.0001) in 2020. We found clinically relevant reductions in CPAP usage with pathway changes post-COVID-19.